Green Marketing: The New Strategic Imperative by Firms in India - Tara, Kanak; Singh, Saumya; Kumar, Ritesh (Indian Journal of Marketing, 2015)
The world has now become a single stage, and we are now moving forward with a common goal of protecting the environment and attaining sustainable development. The green marketing philosophy is getting stronger among the masses, and this attitude of the consumers has forced the business fraternity to rethink and plan their strategies to do their businesses in a more innovative and environmentally friendly way. This has forced the industries to adopt ways and means to sell out their products by way of attracting customers by putting eco-labels and making products more of environmentally friendly in nature. This paper attempted to review green marketing in the Indian context and covered a comprehensive review of literature. Through some examples, it goes on to unearth Indian experiences of green marketing so far. This paper also highlighted future prospects of green marketing in India, and the benefits&stability that it can provide to the society.